A Depicts of Romance in Vikram Seth’s Poems - RAO, S V RAMA (International Journal of Psychosocial Rehabilitation, 2020)
Romanticism affected many forms of art, but it was most important in poetry. In poetry, romanticism is characterized as the rise of individuality and a lyrical appreciation of the natural environment. In their writings, many Romantic writers praised idealism, emotional intensity, and mysticism. In addition, a strong focus on the imagination was put in contrast to the neoclassical tradition, which prioritized science and reason. At its essence, Romanticism is an anti-establishment movement that supports individuality. Individuals should pursue their beliefs rather than existing traditions, according to intellectuals. During the Romantic era, embracing individual liberty became a key poetry topic. William Blake, Lord Byron, and William Wordsworth were all major Romantic writers who used Romantic concepts in their work. Similarly Sri Aurbindo,RavindranathTagore ,Mummad Iqbal and Vikaram Seth are in Indian writings in English.in this described romance inVikram Seth’s poems.